UMP Kilau volunteers help East Coast flood relief - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 21 December 2022 - Universiti Malaysia Pahang (UMP) began mobilising East Coast Flood Volunteering Mission involving 20 UMP Kilau volunteers to lend a helping hand to flood victims in Kelantan and Terengganu.